In-vivo Lens Biometry Using the Novel Ultrasound Biomicroscopy - Ruan, Xiaoting; Liang, Chen; Xia, Zhaoxia; Tan, Xuhua; Jin, Guangming; Jin, Ling; Liu, Zhenzhen; Luo, Lixia (Frontiers in Medicine, 2022)
Background and Aim To assess the reproducibility of the novel ultrasound biomicroscopy, Insight 100 and its agreement with a swept-source optical coherence tomography, CASIA2. Methods A total of 96 volunteers (96 eyes) were enrolled. The radius of anterior lens curvature (RAL), the radius of posterior lens curvature (RPL), lens thickness (LT), and lens diameter (LD) were measured with Insight 100 and CASIA2. A semiautomated software was used to adjust the measurement of LT (LTS) and LD (LDS) by Insight 100. Intraobserver and interobserver reproducibility of Insight 100 measurements, and the agreement of results from Insight 100 and CASIA2 were assessed with 95% limit of agreement (LoA), intraclass correlation coefficient (ICC), Pearson correlation, and linear regression. Results For Insight 100 measurements, the intraobserver ICCs of RAL, RPL, LTS, and LDS measurement were 0.996, 0.973, 0.936, and 0.889, and the interobserver ICCs were 0.987, 0.890, 0.974, and 0.816, respectively. There was an excellent correlation in LT measurements (R = 0.961, P < 0.001) but poor agreements in other parameters between the two devices. The LD measurements tended to be larger (95% CI: 0.768–0.928) in CASIA2 when compared with Insight 100. Conclusion Insight 100 could obtain highly repeatable lens biometry in vivo. With better signal penetration, it shows promising potential in future clinical applications.